PENTA HELIX COLLABORATION DALAM MEWUJUDKAN DAPU (DESA ANTI POLITIK UANG) DI KABUPATEN BANYUMAS - Sari, Yunita Ratna; Angraeni, Windi (PRAJA: Jurnal Ilmiah Pemerintahan, 2025)
This study aims to analyze the penta helix collaboration in realizing DAPU (Anti Money Politics Village) in Banyumas district. This study uses a qualitative descriptive approach by combining various sources of literature, both in the form of primary data and secondary data. The results of the study show that the penta helix collaboration in realizing DAPU (Anti-Money Politics Village) has not run optimally and effectively because there has not been a cooperative relationship in the same forum between the Banyumas Regency Election Supervisory Body (Bawaslu) and the Banyumas Regency KPU as the election organizers, community as the target of the DAPU (Anti Money Politics Village) program, the village government as a facilitator, academics as conceptors and the media in disseminating information related to DAPU. The penta helix actors only work to make the work programs of each agency a success.